2021
DOI: 10.1002/ejp.1793
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting pain processing in adolescents with Non‐Suicidal Self Injury: Could suicide risk lurk among the electrodes?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 89 publications
(124 reference statements)
0
4
1
Order By: Relevance
“…This is consistent with previous study, as Zhou et al (2022) used oddball paradigm to compare the differences of P3b components among NSSI + MDD, MDD and HC groups. Leone et al (2021) used laser evoked potential as an index to study the suicide risk of NSSI adolescents suggest that the amplitude of N2 component in NSSI patients is reduced, which is different from our study, may be due to different experimental paradigms. In this study, no significant difference was found in the latency of N1 between the two groups, which was different from Wen’s study ( Wen et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with previous study, as Zhou et al (2022) used oddball paradigm to compare the differences of P3b components among NSSI + MDD, MDD and HC groups. Leone et al (2021) used laser evoked potential as an index to study the suicide risk of NSSI adolescents suggest that the amplitude of N2 component in NSSI patients is reduced, which is different from our study, may be due to different experimental paradigms. In this study, no significant difference was found in the latency of N1 between the two groups, which was different from Wen’s study ( Wen et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…They were included if they were right‐handed, 22 drug‐naive, had not received cognitive behavioural treatments designed to address NSSI, had a normal cognitive profile (full‐scale IQ ≥ 70, measured using the Wechsler Intelligence Scale for Children), and had a normal or corrected‐to‐normal vision. Adolescents were excluded if they presented organic diseases, schizophrenia, or autism spectrum disorder 23 . Impulsivity was evaluated using (1) the UPPS‐P Impulsive Behavior Scale and (2) the Barratt Impulsiveness Scale Version 11.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents were excluded if they presented organic diseases, schizophrenia, or autism spectrum disorder. 23 Impulsivity was evaluated using (1) the UPPS-P Impulsive Behavior Scale and (2) the Barratt Impulsiveness Scale Version 11. The Multi-Attitude Suicide Tendency Scale and Difficulties in Emotion Regulation Scale were used to assess suicidal tendencies and emotion regulation disorder, respectively.…”
Section: Participantsmentioning
confidence: 99%
“…A red helium-neon (He-Ne) laser confocal with the infrared beam was used to visually indicate the irradiated area. Stimulus energy was fixed at 2 times the perception threshold of warmth on the control side, determined by the method of levels [23], and remained between 34 mJ/mm 2 and 39.6 mJ/mm 2 , which correspond to a stimulation energy of 6 6 to 7 Joules, applied to a skin circle of 15 mm diameter. These parameters allow activating C-warm fibers without concomitant excitation of Aδ axons, and elicit a subjective sensation of 'slow warmness' on normal skin [11,46].…”
Section: -Laser Radiant Innocuous Heat (Stimulation Of C-warmth Fibers)mentioning
confidence: 99%